The Effect of Turmeric Extract (Curcuma Domestica Val) Against the Durability of Yellow Rice Storage - Maha, Hetty Lendora; Sitompul, Erly; silalahi, Jansen (Talenta Publisher, 2019)
Yellow cooked rice is a traditional food in some regions in Indonesia. Yellow cooked rice with the addition of turmeric and flavoring which can longer shelf life of savings because it has antibacterial activity and flavor. The purpose of this study was to determine the effect of turmeric extract (Curcuma domestica Val) to extend shelf life of yellow cooked rice. The samples used were made of yellow cooked rice with handmade and without any seasoning flavored with turmeric extract concentration of 1.8% and 2.4%. Organoleptic testing were conducted every 3 hours, test of microbial growth daily and inhibition of turmeric extract with a concentration of 1.8% and 2.4% of fungi isolated from yellow cooked rice with a total plate count method. Research showed that turmeric extract concentration and the addition of herbs affect the longer shelf life of yellow cooked rice store. High more and more concentration of the turmeric extract can made longer the shelf life of yellow cooked rice either through organoleptic and also total plate count. Yellow cooked rice without seasoning with turmeric extract concentration of 1.8% and 2.4% were 30 and 33 hours respectively, while the yellow cooked rice was flavored with the same concentration of turmeric extract were 36 and 39 hours respectively.